Impact of AI- Powered Translation Tools: Upholding Indian Linguistic Diversity - Krishna, Devina; Gupta, Vadini; Kumari, Kiran; Nidhi, Kumari (Journal of Digital Sociohumanities, 2025)
This paper aims to investigate the transforming potential of AI-driven translating tools in safeguarding and advancing India’s great linguistic variety. By allowing their translation into generally spoken tongues, technologies including Bhashini, Anuvadini, Google Translate, and DeepL are becoming increasingly effective tools for bridging linguistic barriers and reducing the loss of threatened languages. By doing this, these instruments become quite important in preserving cultural identities and guaranteeing the survival of linguistic legacy. This study emphasizes how AI translation tools not only improve efficient communication among many language communities but also greatly help to digital archiving of languages for next generations, so increasing their accessibility and understandable value to more general audiences. This paper shows that AI-driven translating tools not only serve as means of linguistic preservation but also as essential resources for ensuring the continuous relevance and survival of India’s several languages in the digital era by combining a mixed-methods approach—integrating both quantitative survey data collected via WhatsApp and Instagram and qualitative insights drawn from academic articles, web sources. These results have broad ramifications since they highlight the pressing need of legislators, technologists, and cultural players to fund the creation of inclusive, accurate, and sensitive AI language tools. Moreover, the research implies that ensuring that minority and threatened languages are meaningfully reflected in the digital sphere will depend on cooperative efforts among local communities, linguists, and technology developers. This study creates opportunities for future innovation aiming at promoting linguistic equity and cultural sustainability in India and beyond by advancing the debate on the ethical and cultural obligations of artificial intelligence development.